Tingkat Pengungkapan Keberlanjutan (Sustainability Disclosure): Analisis Perbandingan Perusahaan Keuangan dan Perusahaan Non Keuangan Di Indonesia - Herawati Herawati; Yossi Yossi (Jurnal Telaah dan Riset Akuntansi, 2016)
The purpose of the study is to examine and compare sustainability disclosure level of financial companies and non-financial companies in Indonesia. Population of this study is the financial companies listed on the Indonesian Stock Exchange (IDX) and non-financial companies listed on the Jakarta Islamic Index (JII) in period 2014-2015. By using purposive sampling method, it is obtained 17 financial companies and 27 non-financialcompanies. The sustainability disclosure measured by using Global Reporting Initiative (GRI) G4 index. Data analysis technique is using independent sample t-test. Results of the study show that sustainability disclosure level between financial companies and non- financial companiesin 2014 and 2015 is different.  In 2014, sustainabilitydisclosure level between financial companies and non-financial companies is different, while in 2015, there is nodifferences of sustainability disclosure level between financial companies and non- financial companies in Indonesia.KEYWORDS : Global Reporting Initiative G4, Sustainability Disclosure, Finance Company, Non finance company.